PIN ON DISK WEAR TEST ON VARIOUS ALUMINUM ALLOYS - Lahan Asawan, Esa
Wear resistance is one of the critical mechanical properties for materials which accept constant friction, such as gears and ball bearings. Those materials are expected to have a good wear resistant property. One of the techniques used in enhancing wear resistant of a material is increasing the material’s hardness. On this research, wear tests are conducted on several aluminum alloys which have been given treatments, such as alloying, heat treatment, and surface treatment using pin on disk method. The experiment is performed by the same load, rotating speed, and duration on each material, which results in material’s wear loss. The wear resistance value is determined by the value of mass loss. The experiment's result shows that an increased value of aluminum's hardness corresponds to a raise in wear resistance value, which is represented by a decrease in mass loss. Aluminum 2024, with artificial aging process at 190? for 7 hours, has a better wear resistance property than Aluminum 2024 super saturated solid solution. The artificial aging process introduces precipitates which enhance the aluminum's hardness.